1985
DOI: 10.1093/ajcp/83.6.744
|View full text |Cite
|
Sign up to set email alerts
|

Alimentary Tract Ganglioneuromatosis-Lipomatosis, Adrenal Myelolipomas, Pancreatic Telangiectasias, and Multinodular Thyroid Goiter: A Possible Neuroendocrine Syndrome

Abstract: Diffuse, alimentary tract ganglioneuromatosis-lipomatosis, bilateral adrenal myelolipomas, pancreatic telangiectasias, and a multinodular thyroid goiter were found at autopsy in a 56-year-old, white male with a history of insulin-dependent diabetes, hypertension, peptic ulcer, and remote cerebral infarction. The degree of atherosclerosis, arterionephrosclerosis, and cardiac disease found at autopsy did not correlate with the patient's history or his sudden death. The typical features of the multiple endocrine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Although they may be an isolated finding, they are often observed as a component of MEN IIB7 or NF 1 [6]. Hegstrom and Kircher [7] detailed an autopsy case of diffuse gastrointestinal ganglioneuromatosis-lipomatosis. Treatment of GNs depends on the clinical history; polypectomy is curative for polypoid subgroups, but colectomy may be necessary for polyposis or diffuse forms [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although they may be an isolated finding, they are often observed as a component of MEN IIB7 or NF 1 [6]. Hegstrom and Kircher [7] detailed an autopsy case of diffuse gastrointestinal ganglioneuromatosis-lipomatosis. Treatment of GNs depends on the clinical history; polypectomy is curative for polypoid subgroups, but colectomy may be necessary for polyposis or diffuse forms [8].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found a lipoma during colonoscopy. Cutaneous and intestinal lipomas have been detected in a few cases of polyposis [1,3,7] and diffuse GN subgroups. However, they have never been described in the solitary subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…At least two additional patients with ganglioneuromatous polyposis in association with lipomas and various other extraintestinal lesions have been described. The patient of Hegstrom and Kircher [] had the combination of alimentary tract ganglioneuromatosis‐lipomatosis, adrenal myelolipomas, multinodular thyroid goiter, and papillary renal cell carcinoma, and died before PTEN gene testing became available. Several family members had multiple lipomas.…”
Section: Discussionmentioning
confidence: 99%
“…They considered the possibility of Cowden syndrome, but unfortunately, their patient declined genetic testing. The occurrence of renal cell carcinoma in the patient of Hegstrom and Kircher [], as well as the tubular adenomas in the patient of Chan and Haghighi [], and the colon cancer in one of the hamartomatous polyposis patients described by Shekita and Sobin [], certainly raise concern about the possibility of malignancies, which are features in most hamartomatous syndromes. Because this patient also had multiple skin lesions, including lipomas, we felt she best fit into the as yet poorly understood group of ganglioneuromatous polyposis‐lipoma patients (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation